Representation of multiple cellular phenotypes within tissue-level simulations of cardiac electrophysiology - Bowler, Louise A.; Gavaghan, David J.; Mirams, Gary R.; Whiteley, Jonathan P. (Springer, 2018)
Distinct electrophysiological phenotypes are exhibited 1 by biological cells that have differentiated into particular cell types. The usual approach when simulating the cardiac electrophysiology of tissue that includes different cell types is to model the different cell types as occupying spatially distinct yet coupled regions. Instead, we model the electrophysiology of well-mixed cells by using homogenisation to derive an extension to the commonly used monodomain or bidomain equations. These new equations permit spatial variations in the distribution of the different subtypes of cells and will reduce the computational demands of solving the governing equations. We validate the homogenisation computationally, and then use the new model to explain some experimental observations from stem cell-derived cardiomyocyte monolayers.